Humanistic Counseling as a Strategy for Overcoming Low Self-Esteem in Asthmatic Patients - Arinda, Fiska Puspa; Hertinjung, Wisnu Sri; Syakarna, Nugraheni Fitroh R. (Universitas Muhammadiyah Ponorogo, 2023)
The aim of this research is to determine the extent to which humanistic counseling plays a role in overcoming low self-esteem. This research is a case study research on a patient suffering from asthma at a regional hospital in Boyolali. Data collection was carried out using interviews, observation, and psychological testing methods. Based on the results of the assessment that had been carried out, the patient felt limited in carrying out all activities due to her asthma, so this made her even lower in self-esteem. The condition of low self-esteem has many negative impacts on the patient's life, such as being unproductive and limiting social contact with the surrounding environment. Humanistic counseling is one strategy that can help patients overcome low self-esteem. The patient begins to accept her condition and express the positive side of her abilities.